Is there an Association between Vaginal Birth after Cesarean Prediction and Obstetric Anal Sphincter Injury? - Brown, Oluwateniola; Luchristt, Douglas; Miller, Emily S.; Pidaparti, Mahati; Geynisman-Tan, Julia; Kenton, Kimberly; Lewicky-Gaupp, Christina (American Journal of Perinatology, 2020)
Objective This study aimed to estimate whether there is an association between the predicted probability of vaginal birth after cesarean delivery (VBAC) and the occurrence of obstetric anal sphincter injuries (OASIS).Study Design This was a single-site retrospective cohort study of all women with a singleton vaginal birth after a previous cesarean section between January 2011 and December 2016. Women were divided into four ordinal groupings by the predicted probability of achieving vaginal birth after cesarean using the Maternal–Fetal Medicine Units Network VBAC calculator (less than 41%, 40.1–60%, 60.1–80%, and greater than 80%). The primary outcome was OASIS, defined as a 3rd or 4th degree perineal laceration. Bivariable and multivariable analyses were used to examine the association between predicted VBAC probability and OASIS.Results In total, 1,411 women met inclusion criteria and 73 (5.2%) sustained OASIS. The median predicted probability of VBAC was lower in women with OASIS compared with those without OASIS (60% [interquartile range IQR: 48–70%] vs. 66% (IQR: 52–80%), p = 0.02]. On bivariable and multivariable logistic regression, predicted probability of VBAC was associated with increased odds of OASIS (less than 41% probability: adjusted odds ratio [aOR]: 3.18, 95% confidence interval [CI]: 0.90–11.21; 41–60% probability: aOR: 3.76, 95% CI: 1.34–10.57; 61–80% probability aOR: 3.47, 95% CI: 1.25–9.69) relative to women with a predicted probability of VBAC of greater than 80%.Conclusion Having a lower predicted probability of VBAC is associated with an increased risk of OASIS at the time of a VBAC relative to those with greater than 80% predicted probability. Incorporation of this aspect of maternal morbidity may inform risk-stratification at the time of trial of labor after cesarean, as well as the choice of performing an operative vaginal delivery.Key Points
Keywords: OASIS; VBAC; trial of labor